Secure Arithmetic Coding with Error Detection Capability. (19th September 2010) - Sinaie, Mahnaz; Vakili, Vahid Tabataba
Abstract : Recently, arithmetic coding has attracted the attention of many scholars because of its high compression capability. Accordingly, this paper proposed a Joint Source-Cryptographic-Channel Coding (JSCC) based on Arithmetic Coding (AC). For this purpose, embedded error detection arithmetic coding, which is known as continuous error detection (CED), is used. In our proposed method, a random length of forbidden symbol which is produced with a key is used in each recursion. The dummy symbol is divided into two dummy symbols with a key and then is placed in random positions in order to provide security. Finally, in addition to producing secure codes, the suggested method reduced the added redundancy to half of the total redundancy added by CED. It has less complexity than cascades source, channel coding, and encryption while its key space in comparison to other joint methods has enlarged. Moreover, the coder provides a flexible switch between a standard compression model and a joint model.